The Influence of Bullying Characters on the Learning Motivation of Fifth Grade Students of Elementary School 122348 Pematangsiantar - Hia, Ferdinan Henra; Samosir, Alexander (EDUCTUM: Journal Research, 2025)
Bullying behavior is a form of violence carried out by peers and often has a negative impact on the psychological condition and learning process of students. This phenomenon is also seen in fifth grade students of SDN 122348 Pematangsiantar who show symptoms of decreased learning motivation, such as lack of focus, reluctance to ask questions, and withdrawal from class interactions. This study aims to analyze the influence of bullying character on students' learning motivation. The research method used is quantitative with an ex-post facto design, involving 32 students as a sample. Data were collected through questionnaires and analyzed using normality tests, multicollinearity, heteroscedasticity, simple linear regression, and t-tests. The results showed that bullying character has a significant effect on learning motivation, evidenced by the calculated t value of 15.741 which is more than the t table of 2.005 and a significance value of 0.000 which is less than 0.05. The coefficient of determination of 89.2% indicates that variations in learning motivation are strongly influenced by bullying behavior, while 10.8% is influenced by other factors. These findings emphasize the importance of school efforts to prevent bullying in order to create a safe, comfortable learning environment that supports students' academic development.